The Efficacy of Adjuvant Intratympanic Steroid Treatment for Otitis Media with Effusion in Children - Amer, Hazem Saeed; El-Anwar, Mohammad Waheed; Elfeky, Alaa Eldin (International Archives of Otorhinolaryngology, 2016)
Introduction Otitis media with effusion (OME) is a leading cause of hearing impairment in children. Therefore, early and proper management is essential.Objectives The objective of this research is to assess the efficacy of intratympanic (IT) steroids injection for management of otitis media with effusion (OME).Methods This study involved 42 children (84 ears) with bilateral OME. We used tympanometry to confirm the childreńs middle ear effusion and pure tone audiometry to determine hearing threshold. We performed myringotomy and inserted ventilation tubes (VTs) bilaterally, followed by a steroid injection of 0.4–0.6 mL methylprednisolone (40 mg/mL) into one randomly selected middle ear. This procedure was followed by once-weekly administration of steroids (0.5 mL methylprednisolone at a concentration of 40 mg/mL) into the middle ear for three consecutive weeks.Results We found recurrent OME after VT alone in nine (21.4%) ears; whereas, after VT combined with steroid administration, we found two (4.76%), with statistically significant difference. We noted tympanosclerosis postoperatively in six (12.9%) ears and in one of the injected ears (2.3%) (p = 0.0484). Otorrhea occurred in eight (19%) ears with VT alone and in three (7.1%) injected ears, with non-significant difference. The duration between VT insertion and its extrusion was 6.6 = 1.1 months for ears with VT alone and 6.95 =1.12 months in injected ears (p = 0.1541 NS).Conclusion IT Steroids injection for treatment of OME is a safe and simple intervention with lower incidence of symptoms recurrence and postoperative complications. Thus, its use in management of OME is recommended.
Keywords: middle ear effusion; steroid; tympanometry